2019
DOI: 10.1371/journal.pntd.0007369
|View full text |Cite
|
Sign up to set email alerts
|

Tracing the environmental footprint of the Burkholderia pseudomallei lipopolysaccharide genotypes in the tropical “Top End” of the Northern Territory, Australia

Abstract: The Tier 1 select agent Burkholderia pseudomallei is an environmental bacterium that causes melioidosis, a high mortality disease. Variably present genetic markers used to elucidate strain origin, relatedness and virulence in B . pseudomallei include the Burkholderia intracellular motility factor A ( bimA ) and filamentous hemagglutinin 3 ( fhaB3 ) gene variants. Three lipop… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 33 publications
(53 reference statements)
0
21
2
Order By: Relevance
“…All the isolates were also B . pseudomallei BimA allele variant ( bimA Bp ), a further linkage to Southeast Asia [ 23 ]. All B .…”
Section: Resultsmentioning
confidence: 99%
“…All the isolates were also B . pseudomallei BimA allele variant ( bimA Bp ), a further linkage to Southeast Asia [ 23 ]. All B .…”
Section: Resultsmentioning
confidence: 99%
“…Our phylogenetic analysis demonstrated that, despite the ST56 genomes being of Asian origin, the Myanmar ST56s are genetically distinct from those from Bangladesh and Vietnam (separated by 5,688 to 12,103 SNPs-indels) and did not all share a common ancestor, clustering in three phylogenetic locations. This represents another instance of ST homoplasy, which with increasing whole genome analyses is being recognised increasingly and which highlights the limitations of MLST, with unrecognised ST homoplasy suggesting incorrect associations between B. pseudomallei genotypes that confounds analysis of melioidosis epidemiology 39 – 42 . The genetic distance of ST56 genomes from the Australasian node suggests that ST56 may have spread from Vietnam to Myanmar and then from Myanmar on towards Bangladesh, but additional ST56 isolates are needed to confirm this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Burkholderia intracellular motility factor A (BimA) is responsible for actin-based motility of B. pseudomallei 47 and all Myanmar isolates contained the more common bimA Bp , which is typically identified across Asia and has been associated with pneumonia 48 . bimA Bm has only been identified in Australian and Indian isolates and is associated with neurological melioidosis 39 , 48 50 . Filamentous hemagglutinin (fha) is a surface protein that functions as an adhesin 51 .…”
Section: Discussionmentioning
confidence: 99%
“…Their variations have been seen at the genomic, epigenetic, transcriptomic and proteomic levels. Although genome data for human population from melioidois endemic areas is still scarce, genome data for B.pseudomallei has been accumulating ( Holden et al, 2004 ; Hayden et al, 2012 ; Price et al, 2013 , 2016 ; Sahl et al, 2013 , 2016 ; Daligault et al, 2014 ; Bugrysheva et al, 2015 ; Chen et al, 2015 ; Hsueh et al, 2015 ; Johnson et al, 2015a , b ; McRobb et al, 2015 ; Nandi et al, 2015 ; Sidjabat et al, 2015 ; Song et al, 2015 ; Spring-Pearson et al, 2015 ; Viberg et al, 2015 ; Chapple et al, 2016 ; Aziz et al, 2017 ; Chewapreecha et al, 2017 , 2019 ; Podnecky et al, 2017 ; Viberg et al, 2017 ; Webb et al, 2019 ). When combined with spatial and temporal information, this allows further exploration of allelic variants and a shift in allele frequency over space and time.…”
Section: Discussionmentioning
confidence: 99%